2018
DOI: 10.1038/s41467-017-02588-9
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle elasticity directs tumor uptake

Abstract: To date, the role of elasticity in drug delivery remains elusive due to the inability to measure microscale mechanics and alter rheology without affecting chemistry. Herein, we describe the in vitro cellular uptake and in vivo tumor uptake of nanolipogels (NLGs). NLGs are composed of identical lipid bilayers encapsulating an alginate core, with tunable elasticity. The elasticity of NLGs was evaluated by atomic force microscopy, which demonstrated that they exhibit Young’s moduli ranging from 45 ± 9 to 19,000 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
296
2
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 318 publications
(306 citation statements)
references
References 44 publications
5
296
2
3
Order By: Relevance
“…Elasticity of nanoparticles is another feature to direct tumor accumulation. For instance, nanolipogels with a high elasticity (Young's modulus < 1.6 MPa) are preferentially internalized by neoplastic cells whereas the rigid counterparts (Young's modulus > 13.8 MPa) are mainly entrapped within the liver cells . The results from a nanoporous membrane deformability assay and an endothelial barrier assay suggest that the internalization of soft particles depends predominantly on fusion while particles with higher moduli enter cells strictly via clathrin‐mediated endocytosis pathway.…”
Section: Key Features Of Nanoparticles Required For Efficient Cancermentioning
confidence: 99%
“…Elasticity of nanoparticles is another feature to direct tumor accumulation. For instance, nanolipogels with a high elasticity (Young's modulus < 1.6 MPa) are preferentially internalized by neoplastic cells whereas the rigid counterparts (Young's modulus > 13.8 MPa) are mainly entrapped within the liver cells . The results from a nanoporous membrane deformability assay and an endothelial barrier assay suggest that the internalization of soft particles depends predominantly on fusion while particles with higher moduli enter cells strictly via clathrin‐mediated endocytosis pathway.…”
Section: Key Features Of Nanoparticles Required For Efficient Cancermentioning
confidence: 99%
“…To validate this hypothesis, we characterized the nanostructure of ICAM1-FusoNLP and ICAM1-EndoNLG using transmission electron microscopy (TEM) (29). In Figure 2a, it is clear that ICAM1-FusoNLPs feature a soft and hollow lipid bilayer shell, whereas ICAM1-EndoNLGs exhibit a more rigid and crosslinked alginate core inside the lipid bilayer.…”
Section: Resultsmentioning
confidence: 92%
“…In order to facilitate these ICAM1 antibody-directed nanomedicines to enter MDA-MB-231 cells via different cell entry routes, we tuned the particle elasticity of ICAM1-FusoNLP and ICAM1-EndoNLG by encapsulating either PBS (low elasticity) or crosslinked alginate hydrogel (high elasticity), respectively. We previously reported that nanoparticle elasticity directly regulates its cell entry route (29). Here, we hypothesized that ICAM1-FusoNLP and ICAM1-EndoNLG can be engineered with identical particle size, shape, and surface chemistry, and the only viable factor between ICAM1-FusoNLP and ICAM1-EndoNLG is their cell entry routes from receptor-mediated membrane fusion to receptor-mediated endocytosis (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammary epithelial cells and breast cancer cells more avidly took up lipid-alginate particles with lower Young’s moduli (as controlled by alginate crosslinking density). In vivo , the highly flexible lipid-alginate particles successfully targeted tumors in an orthotopic model, while concurrently manifesting reduced liver uptake, relative to rigid counterparts [111]. …”
Section: General Aspects Of Dds Toxicologymentioning
confidence: 99%